Assessment of need and practice for assistive technology and telecare for people with dementia—The ATTILA (Assistive Technology and Telecare to maintain Independent Living At home for people with dementia) trial - Kirsty Forsyth; Catherine Henderson; Lucy Davis; Anusua Singh Roy; Barbara Dunk; Eleanor Curnow; Rebecca Gathercole; Natalie Lam; Emma Harper; Iracema Leroi; John Woolham; Chris Fox; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction The objective of this study was to define current assistive technology and telecare (ATT) practice for people with dementia living at home. Methods This is a randomized controlled trial (N = 495) of ATT assessment and ATT installation intervention, compared with control (restricted ATT package). ATT assessment and installation data were collected. Qualitative work identified value networks delivering ATT, established an ATT assessment standard. Results ATT was delivered by public and not‐for‐profit telecare networks. ATT assessments showed 52% fidelity to the ATT assessment standard. Areas of assessment most frequently leading to identifying ATT need were daily activities (93%), memory (89%), and problem‐solving (83%). ATT needs and recommendations were weakly correlated (τ = 0.242; P < .000), with ATT recommendations and installations moderately correlated (τ = −0.470; P < .000). Half (53%) of recommended technology was not installed. Safety concerns motivated 38% of installations. Discussion Assessment recommendations were routinely disregarded at the point of installation. ATT was commonly recommended for safety and seldom for supporting leisure.